RECONSTRUCTION CADET’S CODE OF CONDUCT AS EFFORTS TO BREAK THE CHAIN OF VIOLENCE / BULLYING TO REMOVE THE HUMAN RIGHTS VIOLATIONS AT MERCHANT MARINE UNIVERSITY IN INDONESIA - Winarno Winarno (Jurnal Pembaharuan Hukum, 2016)
The problems of violence in the world of education is one of the urgent problems obtaining enough sharp spotlight, because in some cases of violence in the educational environment, especially in the merchant marine university  in Indonesian resulting in death. Environmental issues of violence in the Indonesia’s merchant marine university need to be addressed appropriately, especially through the application of disciplinary norms to discipline the cadets.          With the existence of some cases of violence in merchant marine university in Indonesia, saw some of the constraints of handling violence and see that there are many weaknesses in the handling of cases of violence, it is a very important thing to note is the application of norms that discipline is able to accommodate the needs of cadets. Thus norms applicable rules should be tailored to the needs of the various parties involved in the Indonesia’s merchant marine university, as well as to be able to pay attention to happiness and cultivate paradigm corresponding to the shape of the protection of human rights.